THE INFERIORITY COMPLEX OF LAURA WINGFIELD IN TENNESSEE WILLIAMâ€™S THE GLASS MENAGERIE - sumarso, irwan (Dinamika : Jurnal Sastra dan Budaya, 2019)
Abstract: This study analyzes the psychological factors that determine the behaviors of the characters in The Glass Menagerie, especially the character of Laura Wiengfield. Â The study focuses on the inferiority complex of Laura Wingfield in Tennessee Williamsâ€™ The Glass Menagerie. The study analyzes factors and the effects of her inferiority complex seen through the psychological point of view. It analyzes how Lauraâ€™s self-confidence, self-consciousness, fear of embarrassment, and fear of being scrutinized has trigged her social anxiety that makes her experience an inferiority complex.Keywords : inferiority complex, social anxiety, social phobiaÂ Abstrak : Studi ini menganalisa faktor psikologis yang mempengaruhi perilaku para tokoh dalam karya yang berjudul The Glass Menagerieâ€, khususnya karakter tokoh Laura Wiengfield. Studi akan focus menganalisa inferiority complex yang diderita oleh Laura Wingfield dalam karya Tennessee Williams The Glass Menagerie, khususnya pada faktor dan efek dari inferiority kompleks Laura. Studi ini menganalisa rasa percaya diri, kesadaran diri, ketakutan dipermalukan orang lain, yang membuat dia memiliki ketakutan social.Kata kunci : inferiority complex, social anxiety, social phobiaÂ